The complex relationship between colorism and poor health outcomes with African Americans: A systematic review. Issue 1 (26th November 2020) - Keyes, Latocia; Small, Eusebius; Nikolova, Silviya
Abstract: Colorism has a deleterious effect on cognition and health impacting populations. Among African Americans, colorism and social stratification based on skin complexion, has profound sociological effects. These social relationships in daily living show the health burden associated with colorism is enormous. Dark‐skinned African Americans have lower socioeconomic status, diminished prestige, and are less likely to hold elected offices compared to their lighter skin counterparts. This systematic review critically examines a wider scope of effects colorism has on African American adults, a topic not well understood and underexplored. To what extent does colorism impact the psychosocial, educational, and economic outcomes of African Americans? What is the evidence for the efficacy of colorism research associated with poor health? PRISMA guidelines, which consisted of a 27‐item checklist and a four‐phase flow diagram, were used to evaluate research studies. A thematic analysis approach was used to identify and summarize qualitative and quantitative studies. The findings illustrate that African Americans with darker skin are significantly impacted by prejudice solely because of the color of their skin. The multidimensionality of colorism within society for African Americans delineates further damaging impacts on human health. Implications for social and policy changes are discussed.